Karaterisasi Virus Avian Influenza Subtipe H5N1 Isolat Lapang Asal Bali Untuk Kandidat Vaksin - Kencana, Gusti Ayu Yuniati; Suartha, I Nyoman; Kardena, I Made; Nurhandayani, Arini (Jurnal Veteriner; Vol 21 No 4 (2020), 2020)
A research on the isolation and characterization of the Avian Influenza H5N1 subtype field isolate has been carried out at the BSL-3 Laboratory of PT Sanbio Laboratories, Bogor. The aim of the study was to prepare a candidate for the H5N1 subtype Avian Influenza virus vaccine. Virus isolates were taken from field isolates from Bali. A total of seven field H5N1 AI subtypes from Bali were characterized in Bogor. The isolates were: isolate 3A, isolate 4A, isolate 9C, isolate 10 A, isolate 10 C, isolate P65, isolate P67. The passage of isolates was carried out on 9-day-old embryonic Specific Pathogenic (SPF) chicken eggs by injecting 0.1 mL of SPF isolates/eggs through the allantoic cavity. Each isolate was placed in five SPF eggs and then incubated in an incubator at 37 C and candled every day. Since day 2-4 post inoculation, embryo death has occurred. The eggs are harvested by their allantoic fluid and tested for haemagglutination test(HA/HI). The HI test results were confirmed by Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) using the front primer FPHA232_13 (ATTGGTTAYCATGCAAAYAACTCG) and the back primer BPHA232_597 (GGAAAYATAGGTRGTTGGRTTYTGATAG) The results were five of the seven isolates were positive AI subtype B5 585 - 581 The five isolates of AI subtype H5N1 were subsequently sequenced, the results were all positive for AI virus subtype H5N1 clade 2.3.2. Each field isolate was given the name A / Chicken / Bali3A / GAY / 2019; A / Chicken / Bali9C / GAY / 2019; A / Chicken / BaliA4 / GAY / 2019; A / Chicken / Bali10A / GAY / 2016 and A / Chicken / Bali10C / GAY / 2019. One A / Chicken / Bali 9C / GAY / 2016 isolate was subsequently repeated 7 times until a stable H5N1 subtype AI virus titer was obtained. The results of matching with bioinformatics turned out that A / Chicken / Bali 9C / GAY / 2016 isolates had a kinship of 98.62% with AI subtype H5N1 Banyuwangi, amounting to 98.45% with AI subtype H5N1 Lamongan, amounting to 98.10% with AI-H5N1 Lumajang, 97.58% with AI-H5N1 Kediri, 97.07% with AIH5N1 Blitar, 96.72% with AI-H5N1 Denpasar, 96.72% with AI-H5N1 Buleleng and 96.72% with AI-H5N1 Sukoharjo. The conclusion is one of isolate namely A / Chicken / Bali 9C / GAY / 2019 including AI subtype H5N1 clade 2.3.2, is’t stable at passage on SPF eggs, has a kinship of 96.72% with A / duck / Sukoharjo / BBVW-1428- 9/2012, the virus content is 10 6.9 ELD50 so it is potential for vaccine candidates.